Basic theoretical physics : a concise overview - Krey, Uwe. Uwe Krey.; Owen, Anthony, 1945- (Berlin ; New York : Springer, 2007)
This concise treatment embraces, in four parts, all the main aspects of theoretical physics (I . Mechanics and Basic Relativity, II. Electrodynamics and Aspects of Optics, III. Non-relativistic Quantum Mechanics, IV. Thermodynamics and Statistical Physics). It summarizes the material that every graduate student, physicist working in industry, or physics teacher should master during his or her degree course. It thus serves both as an excellent revision and preparation tool, and as a convenient reference source, covering the whole of theoretical physics. It may also be successfully employed to deepen its readers' insight and add new dimensions to their understanding of these fundamental concepts. Recent topics such as holography and quantum cryptography are included, thus making this a unique contribution to the learning material for theoretical physics.
pt. I. Mechanics and basic relativity -- 1. Space and time -- 2. Force and mass -- 3. Basic mechanics of motion in one dimension -- 4. Mechanics of the damped and driven harmonic oscillator -- 5. The three classical conservation laws; two-particle problems -- 6. Motion in a central force field; Kepler's problem -- 7. The Rutherford scattering cross-section -- 8. Lagrange formalism I : Lagrangian and Hamiltonian -- 9. Relativity I : the principle of maximal proper time (Eigenzeit) -- 10. Coupled small oscillations -- 11. Rigid bodies -- 12. Remarks on non-integrable systems : chaos -- 13. Lagrange formalism II : constraints -- 14. Accelerated reference frames -- 15. Relativity II : E=mc[superscript 2] -- pt. II. Electrodynamics and aspects of optics -- 16. Introduction and mathematical preliminaries to part II -- 17. Electrostatics and magnetostatics -- 18. Magnetic field of steady electric currents -- 19. Maxwell's equations I : Faraday's and Maxwell's laws -- 20. Maxwell's equations II : electromagnetic waves -- 21. Applications of electrodynamics in the field of optics -- 22. Conclusion to part II -- pt. III. Quantum mechanics -- 23. On the history of quantum mechanics -- 24. Quantum mechanics : foundations -- 25. One-dimensional problems in quantum mechanics -- 26. The harmonic oscillator I -- 27. The hydrogen atom according to Schrodinger's wave mechanics -- 28. Abstract quantum mechanics (algebraic methods) -- 29. Spin momentum and the Pauli principle (spin-statistics theorem) -- 30. Addition of angular momenta -- 31. Ritz minimization -- 32. Perturbation theory for static problems -- 33. Time-dependent perturbations -- 34. Magnetism : an essentially quantum mechanical phenomenon -- 35. Cooper pairs; superconductors and superfluids -- 36. On the interpretation of quantum mechanics (Reality?, Locality?, Retardation?) -- 37. Quantum mechanics : retrospect and prospect -- 38. Appendix : "mutual preparation algorithm" for quantum cryptography -- pt. IV. Thermodynamics and statistical physics -- 39. Introduction and overview to part IV -- 40. Phenomenological thermodynamics : temperature and heat -- 41. The first and second laws of thermodynamics -- 42. Phase changes, van der Waals theory and related topics -- 43. The Kinetic theory of gases -- 44. Statistical physics -- 45. The transition to classical statistical physics -- 46. Advanced discussion of the second law -- 47. Shannon's information entropy -- 48. Canonical ensembles in phenomenological thermodynamics -- 49. The Clausius-Clapeyron equation -- 50. Production of low and ultralow temperatures; third law -- 51. General statistical physics (statistical operator; trace formalism) -- 52. Ideal Bose and Fermi gases -- 53. Applications I : Fermions, Bosons, condensation phenomena -- 54. Applications II : phase equilibria in chemical physics -- 55. Conclusion to part IV.
Includes bibliographical references (pages 431-433) and index.
English.
Print version record.
Keywords: Physics; Physique; physics; Physics; Physique; Physics